Perdre le fil: labyrinthes de la littérature française moderne - Poirier , Jacques (Amaltea. Revista de Mitocrítica, 2009)
From the day when Theseus killed the Minotaur, the Maze turned into a form in search of meaning, and became useless. As a result, one was enjoined to ascribe nw meanings to the empty strcuture. Modern writers, when confronted with such a void, will have explored all its possibilities: while some of them, like Michel Butor, dismiss the sacred dimensions, others, like Serge Doubrovsky, see in it the image of the self (the body, the psyche...), and others still, like Raymond Roussel, Alain Robbe-Grillet or Georges Pererc, make of the pure geometrical structure of the labyrinth an aesthetic model, and thus a mirror of the work of art. However, one still have to ask whether the labrinth is a valid metaphor for the writing or whether, more accurately, it cannot be the base of a theory of reading.